The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1080/0144929x.2018.1505951
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive work analysis in the conceptual design of first-of-a-kind systems – designing urban air traffic management

Abstract: View related articlesView Crossmark data Citing articles: 1 View citing articles Cognitive work analysis in the conceptual design of first-of-a-kind systemsdesigning urban air traffic management

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 17 publications
(23 reference statements)
0
20
0
Order By: Relevance
“…The present paper introduced a set of widely established CWA phases combined with SNA to refine reduced-crew concept in commercial aviation. In contrary to first-of-a-kind systems (Lundberg et al 2018;Naikar et al 2003) behaviours of the workers in the current system are already well known (Stanton et al 2019). Since the aviation is shaped by legacy systems (Harris and Stanton 2010;Maier 1998) a reduction in crew requires both flight deck function allocation and advanced automation tools.…”
Section: Resultsmentioning
confidence: 99%
“…The present paper introduced a set of widely established CWA phases combined with SNA to refine reduced-crew concept in commercial aviation. In contrary to first-of-a-kind systems (Lundberg et al 2018;Naikar et al 2003) behaviours of the workers in the current system are already well known (Stanton et al 2019). Since the aviation is shaped by legacy systems (Harris and Stanton 2010;Maier 1998) a reduction in crew requires both flight deck function allocation and advanced automation tools.…”
Section: Resultsmentioning
confidence: 99%
“…To promote a safe and workable system in order to provide ease of access to different users, the design needs to have an established robust and flexible way of managing and planning within the desired airspace. The further development of this UTM approach is discussed in [20], [21].…”
Section: Utm In Citiesmentioning
confidence: 99%
“…Bulusu et al showed that cooperation among aircraft greatly improves UAS traffic volumes with simulations in the US San Francisco Bay Area and Norrköping, Sweden [ 25 ]. Lundberg et al addressed challenges of designing future unmanned air traffic management concepts by integrating work domain analysis with conceptual design [ 32 ]. Motlagh et al [ 33 ] presented a comprehensive survey and highlighted the potential for the delivery of low-altitude UAV-based Internet of Things (IoT) services from the air.…”
Section: Literature Review On Management Of Low-altitude Uavsmentioning
confidence: 99%